Do the edge effects influence epicuticular wax production in Vismia guianensis (Aubl.) Choisy (Hypericaceae)? - Santos, Ramôn da Silva; Oliveira, Cássia Alzira Mendes de; Ribeiro, Izabella Maria Cintra; Castro, Shalana Cássia do Nascimento; Sá, Fabiana Cerqueira Nogueira de; Medeiros, Robson Luis Silva de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
Forest fragmentation leads to various environmental problems. It causes edge effects that can decrease biodiversity, promote the growth of lianas, and affect the production of epicuticular wax. This study focuses on examining the secondary metabolites found in the epicuticular wax of Vismia guianensis leaves and investigating the impact of the edge effect on their production. We extracted and quantified the epicuticular wax and analyzed its constituents using gas chromatography coupled with a mass spectrometer. The amount of cuticular wax extracted from V. guianensis leaves ranged from 33.69 to 631.57 μg/cm². Individuals at the forest edge had the lowest wax content, averaging 250.96 μg/cm². On the other hand, individuals located in the interior of the forest had the highest values, with an average of 340.67 μg/cm² per surface unit. The analysis of the samples identified and quantified nine long-chain alkanes (C27 to C35) in the composition of the cuticular wax. The predominant compound in the wax of all individuals was nonacosane alkane (C29). Interestingly, the individuals within the forest fragment exhibited less diversity of compounds compared to those at the forest edge.